0813 Sodium Oxybate Treatment of Narcolepsy in Pediatric Patients: Long-term Efficacy and Safety. (27th April 2018) - Mignot, E; Plazzi, G; Dauvilliers, Y; Rosen, C; Ruoff, C; Black, J; Parvataneni, R; Guinta, D; Wang, Y; Lecendreux, M
Abstract: Introduction: Narcolepsy symptom onset primarily begins in childhood/adolescence. Sodium oxybate (SXB) was evaluated as a treatment for narcolepsy in pediatric patients in a placebo-controlled, randomized-withdrawal study with an open label extension. Results of long-term efficacy and safety assessments are reported. Methods: Children and adolescents with narcolepsy with cataplexy who were on SXB treatment or were SXB-naïve were eligible. After a two-week double-blind, placebo-controlled withdrawal period (DB), participants entered an open-label safety period (OL) for a total study duration of 1 year. Baseline efficacy assessments occurred when participants were on a stable dose of SXB prior to the DB. Change in weekly number of cataplexy attacks was calculated from daily cataplexy diaries. Epworth Sleepiness Scale for Children and Adolescents (ESS-CHAD) was assessed at each visit. Safety evaluations included anxiety (Multidimensional Anxiety Scale for Children 10-item [MASC-10]), depression (Children's Depression Inventory 2nd Edition Self-Report Short Version [CDI 2:SRS]) and suicidality (Columbia-Suicide Severity Rating Scale [C-SSRS]) assessments, and treatment-emergent adverse events (TEAEs). Results: As of the 10 February 2017 datacut: 106 were enrolled; 79 completed ≥6 months and 46 completed 1 year. Efficacy for cataplexy and excessive daytime sleepiness (EDS) was demonstrated after the DB, and was maintained during the OL. The median (Q1, Q3) change from baseline in weekly number of cataplexy attacks was 0.0 (-2.25, 4.17) at study end, with little change throughout. Similarly, among completers, the median (Q1, Q3) change from baseline in ESS-CHAD score was 0.0 (-3.0, 3.0) at study end. No increase of mean T-scores on MASC-10 or CDI 2 was observed. Two serious TEAEs occurred (acute psychosis and suicidal ideation) with both participants endorsing positive responses on the C-SSRS. The most common TEAEs (>10%) were nausea, vomiting, headache, and decreased weight. Conclusion: SXB demonstrated long-term effectiveness (up to 1 year) in reducing cataplexy and EDS in pediatric patients with narcolepsy. The safety profile was consistent with adult studies and no new safety concerns were identified. Support (If Any): Jazz Pharmaceuticals